Phytochemical Fingerprinting, Green Extraction, and Nanobiotechnology of Jahe Emprit (Zingiber officinale var. amarum): A Mini Review - Subakir Salnus (Hayyan Journal, 2026)
Jahe emprit (Zingiber officinale var. amarum) has attracted growing scientific attention because its gingerols, shogaols, zingerone, essential oils, and related metabolites support functional food and phytopharmaceutical development. This review synthesizes recent evidence on phytochemical fingerprinting, green extraction, nanobiotechnological delivery, bioactivities, and translational barriers of jahe emprit and closely related ginger materials. Literature was selected through systematic query expansion, screening, citation chaining, and relevance ranking of studies published mainly between 2017 and 2026. The reviewed studies show that chromatographic, spectroscopic, metabolomic, and chemometric approaches can improve authentication and quality marker identification, especially for 6-gingerol, 6-shogaol, zingerone, alpha-zingiberene, and location-sensitive essential oil profiles. Green extraction methods, particularly supercritical CO2 extraction, microwave-assisted extraction, ultrasound-assisted extraction, and enzyme-assisted extraction, improve yield, selectivity, and bioactive preservation compared with conventional methods. Nanocarriers such as liposomes, polymeric nanoparticles, solid lipid nanoparticles, and plant-derived exosome-like nanoparticles enhance solubility, stability, bioavailability, and targeted delivery in preclinical models. Nevertheless, clinical translation remains constrained by inconsistent quality standards, limited pharmacokinetic data, scale-up uncertainty, regulatory ambiguity, and insufficient long-term safety evidence. Standardized quality markers, reproducible extraction protocols, validated nanoformulations, and rigorous clinical trials are needed to convert jahe emprit from promising bioresource into scalable therapeutic products.